Should I Stop or Should I Go: Early Stopping with Heterogeneous Populations - Adam, Hammaad; Yin, Fan; Hu, Mary; Tenenholtz, Neil; Crawford, Lorin; Mackey, Lester; Koenecke, Allison (NeurIPS 2023, 2023)
Randomized experiments often need to be stopped prematurely due to the treatment having an unintended harmful effect. Existing methods that determine when to stop an experiment early are typically applied to the data in aggregate and do not account for treatment effect heterogeneity. In this paper, we study the early stopping of experiments for harm on heterogeneous populations. We first establish that current methods often fail to stop experiments when the treatment harms a minority group of participants. We then use causal machine learning to develop CLASH, the first broadly-applicable method for heterogeneous early stopping. We demonstrate CLASH's performance on simulated and real data and show that it yields effective early stopping for both clinical trials and A/B tests.